Intraocular Pressure Changes during Femtosecond Laser-Assisted Cataract Surgery: A Comparison between Two Different Patient Interfaces - Chiara De Giacinto; Rossella D’Aloisio; Alessandro Bova; Tommaso Candian; Alberto Armando Perrotta; Daniele Tognetto (Journal of Ophthalmology)
Purpose. The aim of this retrospective cohort study was to evaluate intraocular pressure (IOP) changes during femtosecond laser-assisted cataract surgery (FLACS) using two different patient interface systems. Methods. 116 eyes of 116 patients scheduled for cataract surgery were divided into 2 groups: group 1 (61 eyes) and group 2 (55 eyes) underwent FLACS using Catalys Laser with fluid interface (liquid optics interface, LOI) and LenSx Laser with curved interface and soft contact lens (SoftFit), respectively. IOP was assessed using a portable rebound tonometer (Icare®) preoperatively, after docking, immediately after surgery, at one and seven days postoperatively. Results. In group 1, the mean IOP (±SD) was 14.1 ± 0.4 mmHg before surgery, 33.2 ± 1.1 mmHg after docking, and 21.4 ± 0.9 mmHg immediately after surgery. In group 2, the mean IOP was 13.8 ± 0.4 mmHg before surgery, 24.2 ± 1.4 mmHg after docking, and 20.2 ± 1.2 mmHg immediately after surgery. After the docking procedure, a statistically significant increase in IOP from the baseline was found in both groups (p<0.001). Moreover, no statistically significant difference in IOP measured at 1 and 7 days postoperatively was observed compared with the preoperative values (p>0.05) using both laser platforms. No intraoperative and postoperative complications were observed. Conclusions. FLACS suction phase resulted in a transient increase of IOP in both groups, especially with the LOI system, and it is probably related to the greater pressure of a suction ring and suction generated through the vacuum, independently from the effect of femtosecond laser itself.